Recurrence rate of high-altitude pulmonary edema in lowlanders inducted temporarily to high-altitude areas - I M Pandey; Robin Choudhary; Amit Singh Vasan; Manu Chopra; Anmol Sharma (Wolters Kluwer Medknow Publications, 2024)
Background: Some section of the Indian population resides in high-altitude areas of the mighty Himalayas. In addition to the residents who inhabit mountainous areas, there is also a group of lowlanders who occasionally visit these regions temporarily for work-related purposes or vacations. These individuals are prone to high-altitude illnesses, including acute mountain sickness and high-altitude pulmonary edema (HAPE). This cohort study was undertaken, among acclimatized and nonacclimatized lowlanders based on 3 years of data at a tertiary care hospital, to study the recurrence rate of HAPE in lowlanders. Materials and Methods: The inception cohort consisted of consecutive cases of HAPE among lowlanders, temporarily posted to these high-altitude regions, over 3 years. This cohort was followed up for at least 1 year. The recurrence rate of HAPE in terms of incidence density in person-months and cumulative incidence was calculated, and variables, including clinical features, altitudes at which the symptoms occurred, mode of induction to the high-altitude area, and time of onset of HAPE episodes postinduction altitudes, were studied. Results: The study revealed the recurrence of HAPE as an incidence density of 88.7 per 1000 person-months (95% confidence limit 66.1-115.9 per 1000 person-months). The cumulative incidence was 125 per 1000, over an average follow-up of 22.54 months (95% confidence limit 26-323 per 1000). The study revealed that the recurrence was found to occur at similar altitudes as the previous episode even after following strict acclimatization protocols and slow induction to the high-altitude area by road route with the onset of symptoms within 72 h of entry into the high-altitude area. Conclusion: This study brought out that there is a risk of recurrence of HAPE in lowlanders temporarily inducted to high-altitude areas, with previous episodes of HAPE at similar altitudes as previous episodes, even when acclimatization protocols are followed.